Validation of the EULAR/ACR classification criteria for chronic nonbacterial osteomyelitis in a pediatric cohort - Unal, Dilara; Yigit, Yasemin Demir; Basaran, Ozge; Yildiz, Adalet Elcin; Bayindir, Yagmur; Cam, Veysel; Ozen, Seza (Springer London Ltd, 2025)
ObjectivesChronic nonbacterial osteomyelitis (CNO) is a rare autoinflammatory bone disorder primarily affecting children and adolescents. An international consensus group developed the EULAR/ACR Classification Criteria in order to define a homogeneous group of patients diagnosed with CNO. This study aims to validate these criteria in a diverse pediatric cohort and compare their performance with the Jansson and Roderick diagnostic criteria.MethodsA retrospective evaluation was conducted on 78 pediatric CNO patients and 99 mimickers in Hacettepe University department of pediatric Rheumatology from 2020 to 2024. Demographic, clinical, laboratory, and imaging data were analyzed, and the sensitivity, specificity, and predictive values of the EULAR/ACR criteria were assessed. Statistical comparisons were made against the Jansson and Roderick criteria.ResultsThe EULAR/ACR criteria demonstrated high accuracy, with a sensitivity of 92.68% and specificity of 97.89%, outperforming the Jansson criteria (sensitivity: 88.46%, specificity: 72.73%) and aligning closely with the Roderick criteria (sensitivity: 96.15%, specificity: 96.97%). Key distinguishing features included multifocal and symmetric lesions, frequent involvement of high-scoring anatomical sites (e.g., clavicle and mandible), and the absence of exclusion criteria such as fever and markedly elevated inflammatory markers.ConclusionsThe newly validated EULAR/ACR classification criteria for pediatric CNO demonstrated high specificity and good sensitivity in our cohort. Their application facilitates the identification of homogeneous patient populations, aiding in research consistency and the development of standardized approaches to CNO classification and management.Key Points center dot The EULAR/ACR classification criteria for pediatric CNO exhibited high specificity (97.89%) and sensitivity (92.68%), supporting their validity.center dot Multifocal and symmetric bone lesions, particularly in the clavicle and mandible, strongly support classification under these criteria.center dot Validation in a pediatric cohort reinforces their utility for standardized patient classification and research consistency.ConclusionsThe newly validated EULAR/ACR classification criteria for pediatric CNO demonstrated high specificity and good sensitivity in our cohort. Their application facilitates the identification of homogeneous patient populations, aiding in research consistency and the development of standardized approaches to CNO classification and management.Key Points center dot The EULAR/ACR classification criteria for pediatric CNO exhibited high specificity (97.89%) and sensitivity (92.68%), supporting their validity.center dot Multifocal and symmetric bone lesions, particularly in the clavicle and mandible, strongly support classification under these criteria.center dot Validation in a pediatric cohort reinforces their utility for standardized patient classification and research consistency.
Keywords: Chronic nonbacterial osteomyelitis; Classification criteria; Validation